PENEGEMBANGAN MODUL AJAR PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TEMA AKU CINTA INDONESIA TOPIK TARIAN TRADISIONAL UNTUK ANAK USIA DINI - Sri Yunimar Ningsih,M.Pd; .Ana Novitasari,M.Pd.; Ririn Pitriani (STKIP Subang, 2025)
This research aims to develop a product, namely a Teaching Module for Strengthening the Pancasila Student Profile on the Theme of I Love Indonesia, Topic of Traditional Dances for Early Childhood. The researcher chose a teaching module because it simplifies educators in conducting learning processes. The topic of discussion used in this teaching module is traditional dances, specifically the dolanan dance. The researcher chose the dolanan dance as the topic of discussion here because the students at KB Mekar Sari have enthusiasm in listening to folklore and that blends with art. This type of research is Research and Development (R&D) using the ADDIE development model, which consists of analysis (analyze), design, development, implementation, and evaluation stages. This research was conducted at KB Mekar Sari in the 2024/2025 academic year, semester 2. Data collection techniques used teacher response questionnaires, validation sheets, media expert, content expert, and linguist. The validity results of the teaching module project for strengthening the Pancasila student profile on the theme of I love Indonesia, topic of traditional dances for early childhood, which was carried out by three validators, obtained an average score of 88%, categorized as very valid. The teacher practicality results obtained a score of 95.45% with the category of very practical, and the average effectiveness score obtained a score of 95.45% with the category of very effective. It can be concluded that the teaching module project for strengthening the Pancasila student profile on the theme of I love Indonesia, topic of traditional dances for early childhood, developed by the researcher is suitable for use because it has met the criteria of being valid, practical, and effective.